Tetracycline and sulfonamide residues in commercial egg yolks in the north of Iran - Reza Abolghasemi; Arash Chaichi Nosrati; Leila Modiri; Mirsasan Mirpour (Shahid Beheshti University of Medical Sciences, 2023)
Background: Excessive and anachronous antibiotics using in the food industry and the production of livestock products has resulted in multidrug resistance (MDR) in bacteria against various antibiotics. This study aim was to investigate tetracycline and sulfonamide residues in commercial egg yolks. Methods: Escherichia coli was extracted from 500 egg yolk samples of 37 Iranian brands and tested by phenotypic isolation method and resistance tests for tetracycline, sulfonamide, and nitrofurantoin antibiotics. DNA was extracted from 12 identified multidrug-resistant strains to investigate the molecular mechanism of MDR by PCR with specific primers for tetA, tetB, tetC, tetD, tetG, tetE, tetH, sul I, sul II, sul III, nfsA, and nfsB genes compared to control DNA (ATCC25922). Strains were using the cluster analysis by average Euclidean distance with Jaccard coefficient in SPSS-22. Results: Examination of 12 antibiotic-resistant E. coli by PCR indicated that there were a limited number of resistance genes in the strains. From the group of resistant genes, St2 and St12 strains contained the highest gene number (three genes) and tetracycline-resistant genes were absent in aTcc, St8, St4, and ST3 strains. A maximum of one gene from the sulfonamide-resistant group and one gene for nitrofurantoin-resistance were detected among the studied strains. The highest susceptibility belonged to atcc, St3, and ST8 strains, which were grouped compared to other strains (P-value ≤ 0.05). Conclusion: Manufacturers and managers of the food industry should particularly consider the risk of increased bacterial resistance to antibiotics and implement programs for resistance monitoring to protect human and animal health.